2014
DOI: 10.1155/2014/827827
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Autoimmune Response in Prostate Cancer to Cyclin B1 in a Panel of Tumor-Associated Antigens

Abstract: Previous studies have demonstrated that sera from patients with prostate cancer (PCa) contain autoantibodies that react with tumor-associated antigens (TAAs). Autoantibodies to cyclin B1 and fourteen other TAAs were detected by enzyme-linked immunosorbent assay (ELISA) and Western blotting in 464 sera from patients with PCa, benign prostatic hyperplasia (BPH), and other controls. Autoantibodies to cyclin B1 were detected in 31.0% of sera from randomly selected patients with PCa versus 4.8% in sera with BPH. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
(59 reference statements)
4
22
0
Order By: Relevance
“…We also confirmed the spontaneous CCNB1-specific IgG response observed in healthy and cancer patients (30,31,(53)(54)(55)). We observed a similar level of anti-CCNB1 Abs in patients and healthy donors (31).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We also confirmed the spontaneous CCNB1-specific IgG response observed in healthy and cancer patients (30,31,(53)(54)(55)). We observed a similar level of anti-CCNB1 Abs in patients and healthy donors (31).…”
Section: Discussionsupporting
confidence: 84%
“…We observed a similar level of anti-CCNB1 Abs in patients and healthy donors (31). This is at variance with other studies in which the level was either higher (53,54) or lower (55) in cancer patients than in healthy donors. These discrepancies may result either from cancer indications or from a strong variation between individuals, as revealed in Fig.…”
Section: Discussionsupporting
confidence: 66%
“…A recent study identified cyclin B1 [36] as an important antibody target in prostate cancer but also in early PSA negative stage of disease [37]. A new study in asymptomatic monoclonal gammopathy (AMG) identified potential targets for prevention of multiple myeloma (MM).…”
Section: Candidate Antigens For Preventative Vaccinesmentioning
confidence: 99%
“…Finally, another promising source of vaccine antigens are those targeted by spontaneous anti-tumor immune responses. Two such antigens, Cyclin B1 and SOX2, are found to be common targets of spontaneous immune responses for lung and prostate premalignant lesions and MGUS and MM, respectively (Dai et al, 2014; Kao et al, 2001; Spisek et al, 2007). …”
Section: Prophylactic Cancer Vaccinesmentioning
confidence: 99%